2019
DOI: 10.3390/su11071941
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Exclusion, a Choice between Biomass Growth and Species Diversity Maintenance in Beijing—Tianjin Sand Source Control Project

Abstract: Grasslands in northern China form an important ecological barrier that prevents and controls desertification. The Beijing–Tianjin Sand Source Control (BTSSC) Project has been implemented to restore grassland in order to control sand sourced pollution. This study aimed to understand the impacts of four applied restoration practices on the productivity, composition, and species diversity of vegetation communities in the BTSSC Project. The results indicated the following: (1) All the restoration practices tended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The overestimation would be further exaggerated if the models were calibrated using the normal-year data only, as in previous efforts [8,25,29]. The GPP reduction caused by drought might have been slightly underestimated at the XL site in this study due to ignorance of the possible vegetation recoveries after grazing exclusion [115] (Table 2). It should be noted that although the current water stress indicators, such as EVI, cannot fully capture the GPP responses to drought, they can still be used to monitor the drought effects, especially over large areas where no other information is available [116].…”
Section: Varying Performances Of the Eight Satellite-based Gpp Modelsmentioning
confidence: 65%
“…The overestimation would be further exaggerated if the models were calibrated using the normal-year data only, as in previous efforts [8,25,29]. The GPP reduction caused by drought might have been slightly underestimated at the XL site in this study due to ignorance of the possible vegetation recoveries after grazing exclusion [115] (Table 2). It should be noted that although the current water stress indicators, such as EVI, cannot fully capture the GPP responses to drought, they can still be used to monitor the drought effects, especially over large areas where no other information is available [116].…”
Section: Varying Performances Of the Eight Satellite-based Gpp Modelsmentioning
confidence: 65%
“…Through the processes of wind erosion and salinization, desertification has caused many detrimental effects on the environment and social economy [11]. A series of desertification control projects (DCPs) represent China's great efforts to combat desertification, such as the Grain for Green Project, the Natural Forest Conservation Project, and the Beijing-Tianjin Wind and Sand Source Control Project [12,13]. At the same time, many lower-level governments have also carried out a number of projects to control desertification on the basis of regional characteristics, which are complementary to the central government's projects [14].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there was an increase in the species diversity of herbaceous plants 24 . A decrease in species diversity with increasing elevations is a more familiar pattern for herbaceous plants in temperate 56 and tropical 22 forests.…”
Section: Discussionmentioning
confidence: 99%
“…The major factors that control the distribution areas of species differ among different families and genera, and thus the vertical distribution patterns of species diversity differ 22 . We concluded that the family number of the tree species had a maximum distribution at lower elevations, unlike herb and shrub species; meanwhile, the responses of the importance values to the altitudinal gradient in the tree community were also different among evergreen coniferous trees, deciduous coniferous trees, and deciduous broad-leaved trees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation